Morphologie urbaine et mobilité dans la Communauté Urbaine de Strasbourg - Dong-Binh Tran (Unité Mixte de Recherche 8504 Géographie-cités, 2014)
This paper empirically examines the relationships between urban morphology and travel behavior in the agglomeration of Strasbourg. Urban morphology is measured by built-up and network indicators while mobility and socio-economic characteristics are obtained from the Household Travel Survey (EMD – Enquête ménages déplacements) of Certu (French Centre for the Study of Urban Planning, Transportation and Public Facilities). The built environment indicators based on landscape metrics constitutes our original approach. These indicators are then used in statistical tests to specify relationships between urban morphology and mobility according to urban context. Some morphological indicators of proximity and fragmentation of form of buildings complete socio-economic characteristics to explain urban mobility.